The differential effects of Jesus and God on distributive behaviour - Lane, Tom (University of Nottingham, 2019)
This study shows that different belief concepts within the same religion can have different effects on distributive behaviour. A dictator game experiment measures the causal effects of the concepts of God and Jesus on both the pro-sociality of Christians and their propensity to discriminate against LGBTQ people. The concept of Jesus significantly raises the amounts Christians donate, but the concept of God does not. Christians are found, at borderline significance, to discriminate against LGBTQ people, but this discrimination is not significantly increased by the concepts of Jesus or God. Neither concept significantly affects the behaviour of a non-Christian sample.